Optical Proxies for Terrestrial Dissolved Organic Matter in Estuaries and Coastal Waters - Osburn, Christopher L.; Boyd, Thomas J.; Montgomery, Michael T.; Bianchi, Thomas S.; Coffin, Richard B.; Paerl, Hans W. (Frontiers in Marine Science, 2016)
Optical proxies, especially DOM fluorescence, were used to track terrestrial DOM fluxes through estuaries and coastal waters by comparing models developed for several coastal ecosystems. Key to using optical properties is validating and calibrating them with chemical measurements, such as lignin-derived phenols - a proxy to quantify terrestrial DOM. Utilizing parallel factor analysis (PARAFAC), and comparing models statistically using the OpenFluor database (http://www.openfluor.org) we have found common, ubiquitous fluorescing components which correlate most strongly with lignin phenol concentrations in several estuarine and coastal environments. Optical proxies for lignin were computed for the following regions: Mackenzie River Estuary, Atchafalaya River Estuary, Charleston Harbor, Chesapeake Bay, and Neuse River Estuary. The slope of linear regression models relating CDOM absorption at 350 nm (a350) to DOC and to lignin, varied 5 to 10 fold among systems. Where seasonal observations were available from a region, there were distinct seasonal differences in equation parameters for these optical proxies. Despite variability, overall models using single linear regression were developed that related dissolved organic carbon (DOC) concentration to CDOM (DOC = 40×a350+138; R2 = 0.77; N = 130) and lignin (Σ8) to CDOM (Σ8 = 2.03×a350-0.5; R2 = 0.87; N = 130). This wide variability suggested that local or regional optical models should be developed for predicting terrestrial DOM flux into coastal oceans and taken into account when upscaling to remote sensing observations and calibrations.